Appraisal of Land Fragmentation and Crop Production in the Western Terai of Nepal (Pragnya Sarathi, 2026)
Land disintegration is a widespread distinctiveness of all farming systems that influences farmland efficiency. The relationship between farm size and productivity in developing countries is one of the oldest issues in the academic literature on agrarian structure. The main objective of this research was to assess the land fragmentation condition and its relation to crop production in the western Tarai of Nepal. This study was based on mixed methods that adopted both qualitative and quantitative methods, including primary and secondary sources of information. In addition to field observation, a total of 124 household surveys, 13 key informant interviews, and 6 focus group discussions were conducted for primary data, and census data from the national statistical office and profile data from the municipality were used for secondary information. Apart from these, topographic maps, cadastral maps, and satellite imagery were used for ground verification. It was concluded that land fragmentation triggered the loss in productivity; however, it was noted that the gain in production was tracked by intensive cropping practices. Out of the total, 69.4 percent of respondents identified a loss, and 30.6 percent reported a gain in productivity. It is recommended to utilize systematic land use planning and follow crop diversification, multiple cropping, and intensive farming, which could be an alternative to mitigate farm land fragmentation and increase productivity.